Investigation of in-depth and surface properties of polyethyleneterephthalate thin films after SHI and gamma radiation treatment by means of PALS and AFM studies. (May 2015) - Singh, Paramjit; Kumar, Rajesh; Nambissan, P.M.G.
Abstract: Positron annihilation lifetime spectroscopy (PALS) and atomic force microscopy (AFM) analyses were adopted for in-depth (at the nanoscale level) and surface (at the microscale level) understanding of the swift heavy ions (SHI) irradiated and radiation exposed polymer films. Polyethyleneterephthalate (PET) polymer films were irradiated by 70 MeV C 5+ ions to the fluences ranging from 1 × 10 11 to 5 × 10 12 ions/cm 2 . The other set of PET films were exposed to gamma radiation emitted by 60 Co source at various doses ranging from 250 to 1250 kGy. The Tao-Eldrup model was used to calculate the value of hole radius (R), free volume (FV) and fractional free volume (FFV) from the lifetime and intensity values of ortho-positronium (o-Ps) as obtained from the PALS spectra. These parameters (R, FV and FFV) were analyzed to study the in-depth modification of the polymer after ion beam and gamma radiation treatment. The AFM studies reveal the surface modifications in the ions irradiated and gamma radiation exposed polymer films. In addition to these studies; the structural, optical and chemical properties were studied by X-ray diffraction (XRD), UV–visible (UV–vis) and Fourier transform infrared (FTIR) spectroscopy respectively. The XRD spectra showed improved crystalline nature of the polymer after ion beam irradiation as well as gamma radiation exposure. The optical absorption spectra showed a shift in the absorption edge towards higher wavelength side. The band gap energy was calculated using Tauc's relation, which indicated a significant decrease in the value of band gap of the polymer films in both the cases (C 5+ ions and gamma radiation). The FTIR spectra obtained after irradiation exhibits increment of the intensities of the typical vibrational bands. Highlights: Carbon ion irradiation and gamma radiation exposure of polyethyleneterephthalate polymeric thin films. The study of modification of the nano scale free volume by means of PALS technique. XRD, UV–vis, FTIR and AFM studies for structural, optical, chemical and surface modifications. Estimation of hole radius (R), free volume (FV) and fractional free volume (FFV) using Tao-Eldrup model.